P258 Incidence of Histoplasmosis, Cryptococcosis, and TB Among People Living with HIV in Paraguay-Preliminary Report. (20th September 2022) - Samudio, Tania; Aguilar, Gloria; Sued, Omar; López, Gladys; Jordan, Alexander; Cáceres, Diego H.; Ovelar, Patricia; Cardozo, Miguel; Vicenti, Cristina; Lezcano, Virgilio; Pereira, José; Rios-Gonzalez, Carlos; et al.
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objectives: Endemic fungal infections such as Histoplasmosis and Cryptococcosis as well as tuberculosis (TB) are important causes of mortality among people living with HIV (PLHIV) in Latin America. Rapid diagnostic assays (RDAs) could decrease the time to diagnosis and treatment of these infections, resulting in a reduction in mortality. The objectives of this study were to determine the incidence of Histoplasmosis, Cryptococcosis, and TB using RDAs in PLHIV with advanced HIV disease (AHD) and calculate 30-day mortality. Methods: PLHIV 18 years and older, treated at the Institute of Tropical Medicine hospital in Asuncion, Paraguay, not receiving ART and presenting CD4 count ≤ 200 cells/μL or clinical symptoms suggestive of WHO stage 3 or 4 diseases were enrolled and followed for 30 days. Detection of Histoplasma Ag (HisAg) in urine was performed by enzyme immunoassay (EIA), Cryptococcus Ag (CrAg) detection in serum and cerebrospinal fluid specimens by lateral flow assay (LFA), and liparabinomannan (LAM) detection in urine by LFA (TB LAM) (limited to those patients with CD4 counts ≤ 100 cells/μL) and by GeneXpert (limited to patients with respiratory symptoms). Results: From August 2021 to 25 March 2022, a total of 335 PLHIV were enrolled. Patient median age was 37 years [Interquartile Range (IQR) 16 years], median CD4 count at enrollment was 91 cells/ μ L (IQR 147 cell/ μ L). A total of 80% ( n = 269) of patients were symptomatic for one or more of the three diseases being screened for. Ag positivity rate was 20% (40/196) for TB-LAM, 10% (32/314) for HisAg, and 11% (35/329) for CrAg (15 diagnosed with cryptococcal meningitis). GeneXpert testing showed a positivity of 14% (15/108), and six of these patients with positive GeneXpert also tested positive for TB-LAM. In total, 100/335 (30%) of patients tested had a positive result and coinfections were observed among 14/335 (4.2%) patients (Table 1). Histoplasmosis + TB was the most frequent co-infection observed 12/335 (3.6%). Mortality among those who completed 30-day follow-up was 12.6% (32/254) and 11% among those with an OI (11/102) Conclusions: Preliminary results show that TB and fungal opportunistic infections, including co-infection were common in people with advanced HIV. Longitudinal follow-up will help to evaluate the feasibility and cost of implementing RDAs for the early detection of opportunistic infections in PLHIV with AHD in Paraguay. Early diagnosis could impact mortality reduction.